Culturas juvenis e educação escolarizada: movimentos culturais com jovens em contextos empobrecidos - Oliveira, Flavio Goncalves de (2023)
The research examines cultural movements with young people in impoverished school contexts, based on experiences formed in a public state school located in the municipality of Cariacica/ES, and is linked to the Professional Master's Program in Education at the Education Center of the Federal University of Espírito Santo. In dialogue with youth, the study is based on theorists (Abramo, 1996; Foracchi, 2018; Groppo, 2000, 2004, 2015, 2016, 2017; Pais, 1990, 2003; Peralva, 1997) who understand youth as a historical-social construction influenced by other social variables such as gender, race, and social class. To understand how poverty affects young people, the investigation refers to theses (Cararo, 2015; Carneiro, 2005; Codes, 2008; Nascimento, 2013) that broaden the understanding of this condition beyond material deprivation, analyzing it as a multidimensional and complex phenomenon that impacts the lives of thousands of people who are victims of different forms of violence and violations of rights. The analysis begins with a critique of the charitable and moralistic conception of poverty (Arroyo, 2012, 2013, 2014, 2015, 2019a, 2019b), which is present in the relationship between schooling and these subjects, and seeks to broaden perspectives on the youth cultures that exist in schools, recognizing their practitioners as socio-cultural subjects with their own knowledge and values (Dayrell, 2003, 2005, 2007, 2011, 2016). Through a qualitative approach, grounded in action research (Barbier, 2002; Franco, 2005; Pimenta; Franco, 2012; Thiollent, 2009; Trip, 2005), and systematized through cultural movements with the participating young people, the research establishes critical-reflective conversations with the collective about the issues that affect the youth condition in contexts where life is precarious. It also discusses how school spaces/times reinforce stereotypical images of impoverished youth, contributing to the perpetuation of many dependencies. In contrast, the research believes in the collective construction of knowledge through dialogue with the typical knowledge of the youth universe, such as artistic-cultural languages. Based on dialogic movements, concludes that it is possible to establish more democratic pedagogical practices that respect youth sociabilities and provide educational paths that are closer to what young people actually experience and feel.